Radar return reduction for wind turbines using bump structures - Shyh, Kuang Ueng; Yao, Hong Chan; Wei, Hsien Lu; Heng, Wen Chang (Universiti Kebangsaan Malaysia, 2015)
Wind turbines are massive electrical structures. They produce large returns when illuminated by radar waves. These scatterings have a great impact on the operation of surveillance, air traffic control and weather radars. This paper presents two geometric modelling methods for reshaping wind turbine towers so that the Radar Cross Section (RCS) of wind turbines is reduced. In the proposed reshaping methods, bump structures are created on the surface of the conventional cylinder wind turbine tower. When a reshaped tower is illuminated by radar waves, the bump structures scatter incident radar waves into insignificant directions so that the strength of back-scattering is declined and the RCS of the wind turbine is decreased. The test results confirmed that the proposed methods significantly reduce bi-static RCS values of wind turbines. The proposed reshaping methods are practical, flexible and effective in alleviating the scatterings of wind turbines.